2024
DOI: 10.3847/1538-4357/ad0463
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Polarization to Grain Shape. I. Convex Shapes

B. T. Draine

Abstract: Aligned interstellar grains produce polarized extinction (observed at wavelengths from the far-ultraviolet to the mid-infrared) and polarized thermal emission (observed at far-infrared and submm wavelengths). The grains must be quite nonspherical, but the actual shapes are unknown. The relative efficacy for aligned grains to produce polarization at optical versus infrared wavelengths depends on particle shape. The discrete dipole approximation is used to calculate polarization cross sections for 20 different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…If the Telesco et al (2022) result for p p sil max D is confirmed, any grain model (e.g., the astrodust model) that posits a single grain component dominating both starlight polarization and farinfrared emission would appear to be ruled out. However, Draine (2024) has argued that Cyg OB2-12 may have significant intrinsic (apparently time-variable) polarization, complicating determination of the interstellar contribution to the polarization. More polarimetry of Cyg OB2-12 in the optical and mid-IR is needed to confirm the determination of p p sil max D for interstellar dust.…”
Section: μM Polarizationmentioning
confidence: 99%
“…If the Telesco et al (2022) result for p p sil max D is confirmed, any grain model (e.g., the astrodust model) that posits a single grain component dominating both starlight polarization and farinfrared emission would appear to be ruled out. However, Draine (2024) has argued that Cyg OB2-12 may have significant intrinsic (apparently time-variable) polarization, complicating determination of the interstellar contribution to the polarization. More polarimetry of Cyg OB2-12 in the optical and mid-IR is needed to confirm the determination of p p sil max D for interstellar dust.…”
Section: μM Polarizationmentioning
confidence: 99%